2021
DOI: 10.31098/ijmesh.v4i1.494
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Academic Self-Efficacy and Its impact on perceived Academic Burnout among Students in Bangladesh.

Abstract: For this present study, COR and SCT theory was used firstly to examine the factors related to academic burnout meanwhile, secondly, this research also attempts to examine the factors related to academic self-efficacy and Finally, to identify the relationship between academic self-efficacy academic burnout in Khulna city, Bangladesh. For this present study data was collected via both E-mail and self-administrative questionnaire from 272 university students. From the research findings and analysis, it was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The study revealed that students who have higher self-efficacy feel less depressed and exhibit less emotional exhaustion. Academic self-efficacy is a trait present in students and, due to academic reasons most students face a large amount of burnout ( Akter, 2021 ). Long hours of studying during quarantine may contribute to a decrease in academic self-efficacy, further increasing the levels of burnout, which can lead to substance abuse and moderate to high rates of depression ( Janko and Smeds, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that students who have higher self-efficacy feel less depressed and exhibit less emotional exhaustion. Academic self-efficacy is a trait present in students and, due to academic reasons most students face a large amount of burnout ( Akter, 2021 ). Long hours of studying during quarantine may contribute to a decrease in academic self-efficacy, further increasing the levels of burnout, which can lead to substance abuse and moderate to high rates of depression ( Janko and Smeds, 2019 ).…”
Section: Discussionmentioning
confidence: 99%